2016
DOI: 10.3341/kjo.2016.30.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Platelet-rich Plasma Eye Drops in the Treatment of Recurrent Corneal Erosions

Abstract: PurposeTo evaluate the effect of platelet-rich plasma (PRP) eye drops in the treatment of recurrent corneal erosions (RCE).MethodsA total of 47 eyes were included in this retrospective study. Clinical records of 20 consecutive patients with RCE who had been treated with conventional lubricant eye drops (conventional treatment group) from June 2006 to December 2008 and 27 consecutive patients treated with autologous PRP eye drops in addition to lubricant eye drops (PRP eye drops treated group) from January 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 33 publications
1
35
0
1
Order By: Relevance
“…The aim of this study was to evaluate the effectiveness of intrauterine infusion of PRP in the treatment of thin endometrium in FET cycles (El-Anwar et al. , 2016; Lee et al. , 2016; Maria-Angeliki et al , 2015; Picard et al , 2015; Ronci et al , 2015; Rossi et al , 2016; Sadabad et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to evaluate the effectiveness of intrauterine infusion of PRP in the treatment of thin endometrium in FET cycles (El-Anwar et al. , 2016; Lee et al. , 2016; Maria-Angeliki et al , 2015; Picard et al , 2015; Ronci et al , 2015; Rossi et al , 2016; Sadabad et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The oil present in the serum may act as a suitable substitute for the lipid components produced by Meibomian glands, and pre-albumin contributes to the stability of the tear film. Clinical trials have shown that autologous serum can be used to effectively treat RCE [35].…”
Section: Measures To Treat Recalcitrant Corneal Erosionsmentioning
confidence: 99%
“…In 1984, its first successful use in patients with dry eye was described [ 19 ]. However, from the works of Tsubota et al [ 20 , 21 ] in 1999, AS application gained widespread acceptance as an adjuvant therapy in different ocular surface disorders [ 3 , 15 , 22 , 23 ].…”
Section: Hemoderivativesmentioning
confidence: 99%
“…The therapeutic advantages of AS use as a substitute for tears are given by their similarity in certain characteristics, such as pH, osmolality, and biomechanical characteristics. AS fulfills a lubricating function and performs anti-inflammatory, antimicrobial, and epitheliotrophic functions through certain biomolecules of its composition similar to natural tears [ 13 , 23 ] ( Table 1 ).…”
Section: Hemoderivativesmentioning
confidence: 99%
See 1 more Smart Citation